Panel Dinding Pracetak dari Limbah Pukat dan Serabut Kelapa Berlapis Resin Polyester dengan Motif Desain Glow in the Dark - Mia Sofiatus Solikah; Riza Susanti; Shifa Fauziyah (Jurnal Sipil dan Arsitektur, 2024)
Using concrete blocks, light bricks, red bricks, thick plastering, and action affects the cost budget. This encouraged the author to create wall panels that are ready to install and do not require mortar mix in finishing. Along with this, trawl and coconut fiber waste were the main materials used in making wall panels, and an additional M6 wire mesh iron was used as reinforcement for the construction. The outermost layer was coated with SHCP 2668 clear polyester resin and catalyst combined with phosphorus strontium aluminate powder and metallic pigment coloring. The method used in this research is the experimental method by making four compositional comparisons for each test with three test objects each. The results of this study are the most optimum composition in a mixture of 1.5: 2.75: 1.5, which has a compressive strength of 13.5 N/mm2 and flexural strength of 2.49 N/mm2 by SNI 03-3122-1992, is ductile, reflective, has a sound absorption of 0.290 dB by ISO10534-2 testing: 1998, water absorption (DSA) of 0.91% by SNI 03-0349-1989, fire resistance at a rate of 0.22 mm/second by modified SNI 1741-2008 testing, able to emit light for 2-3 hours from a 20-minute lighting source by JIS Z 9107 and JIS Z 9095 testing, and has a lower price than other wall panels.